Social Cohesivity of The Indonesian Muslim Community During the Ramadan - Shalihin, Nurus; Yusuf, M; Hulwati, Hulwati (Islam Realitas: Journal of Islamic and Social Studies, 2023)
This study aims to analyze the social cohesiveness of Indonesian Muslim communities during Ramadan. Moral sense, sense of belonging, social har mony, sense of security, and tolerance in this study are used as indicators to understand social cohesiveness.Â  Data were collected through questionnaires with 600 respondents randomly selected in three districts/cities in West Sumatra and Yogyakarta provinces. The study found that two indicators of social cohesion were in the high category, namely a sense of morality (3.39 or 84.75%) and social harmony (3.30 or 82.50%), while three other indicators of social cohesion were in the medium category, namely a sense of belonging (2.34 or 58.50%), a sense of security (2.54 or 63.50%), and tolerance (2.70 or 67.50%). Thus, the social cohesion of the Muslim community during Ramadan is in the moderate category, with an average of 2.85 or equivalent to 71.17 percent. This study concludes that Ramadan has not contributed significantly to building social cohesiveness. The ambiguity of faith, which is ambiguous in understanding reality; sacred and profane, can be identified as one of the reasons why Ramadan has not been able to build social cohesiveness.